The Effect of Imposter Syndrome on Athletes’ Self-Confidence in Individual Sports - Bayu Rifqi Rela; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Salma Maharani Sopandi (Universitas Negeri Semarang, 2026)
In the world of sports, athletes often experience a psychological phenomenon known as impostor syndrome. Impostor syndrome is a phenomenon in which a person with a strong track record of achievements feels they have deceived others regarding their skills, doubts their own abilities, and believes that their success is due to external factors; this can negatively impact the athlete’s self-confidence. This study aims to examine the prevalence of the Impostor Syndrome phenomenon among individual athletes and to determine the impact of Impostor Syndrome on the self-confidence of individual athletes. A descriptive method with a quantitative approach was used in this study, which involved 24 individual athletes aged 18–25 years. The instruments used in the study consisted of two questionnaires: the Clance Impostor Phenomenon Scale (CIPS) and the Athlete Self-Confidence Questionnaire (ASQ), which were administered once to the sample. After the data were collected, data analysis was performed using the correlation test in SPSS Version 29. The results of the study indicate that impostor syndrome influences competitive self-confidence in individual athletes. Based on the results, it can be concluded that impostor syndrome has a significant effect on athletes’ self-confidence. The higher the level of impostor syndrome experienced by athletes, the lower their level of self-confidence and the higher their level of anxiety